Deconstruction of Radical Thought in Islam: Nurcholish Madjid's Moderate Intellectualism Strategy in The Contemporary Era - Airohmah, Yesi; Rahmawati, Nafisah; Muthohar, Ahmad (IAIN Kendari, 2025)
This article aims to critically examine Nurcholish Madjid's strategy of moderate intellectualism as a form of deconstruction of radical thought in Islam in the contemporary era. This research uses the library research method, which is a method that aims to examine literature in depth, both primary and secondary. Primary data was collected from Nurcholish Madjid's writings such as books, articles, and relevant papers. Meanwhile, secondary data were obtained from scientific journals, the results of previous research, and literature on radical Islamic ideology and moderation. The results of the study show that Cak Nur's intellectual strategies, such as political desacralization, positive secularization, rationalization of religious teachings, and the strengthening of pluralism and democracy, are able to dismantle the ideological structure of radicalism based on textual and exclusive interpretations. This moderate approach not only offers a more contextual and humanist Islamic narrative, but also serves as a strategic response in strengthening an inclusive, tolerant, and peaceful Islamic discourse in the midst of the complexity of the challenges of the times.